2008
DOI: 10.1016/j.vaccine.2007.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Infection of monocytes or immature dendritic cells (DCs) with an attenuated rabies virus results in DC maturation and a strong activation of the NFκB signaling pathway

Abstract: To assess the potential role of dendritic cells (DCs) or monocytes in the development of a protective immune response, we infected human immature DCs or monocytes with a live rabies virus (RV) vaccine strain (SPBNGAS-GAS) and a pathogenic RV (DOG4). Both cell types were infected with SPBNGAS-GAS and DOG4 and both RVs were similarly potent in inducing maturation of immature DCs or monocytes. However, in contrast to DOG4, SPBNGAS-GAS induced very high levels of IFN-alpha1 mRNA in monocytes and DCs. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 26 publications
4
50
0
Order By: Relevance
“…The recombinant RV vaccine SPBNGAS is based on the prototype recombinant virus SPBN, which was derived from the SAD B19 cDNA clone (17). The generation of the double G variant of SPBN is described elsewhere (12,13). All RV vaccine strains were propagated in BSR (a BHK-21 clone) (18) cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant RV vaccine SPBNGAS is based on the prototype recombinant virus SPBN, which was derived from the SAD B19 cDNA clone (17). The generation of the double G variant of SPBN is described elsewhere (12,13). All RV vaccine strains were propagated in BSR (a BHK-21 clone) (18) cells.…”
Section: Methodsmentioning
confidence: 99%
“…The G containing both mutations has been designated as GAS. Using the GAS gene, the single and double GAS RV variants, SPBNGAS and SPBNGAS-GAS, respectively, were constructed (10,12). The introduction of a second G gene significantly improves the efficacy of the vaccine by enhancing its immunogenicity through higher expression of G (13).…”
mentioning
confidence: 99%
“…Previous results indicate that both murine and human dendritic cells can be infected and activated by RABV (19,20,34), and such cells are widely used to study inflammasome activation. Therefore, we first determined whether IL-1␤ was activated and secreted in BMDCs from mice after infection with RABV.…”
Section: Il-1␤ Is Secreted After Rabv Infectionmentioning
confidence: 99%
“…RABV activates antiviral immune responses in BMDCs via the adaptor protein IPS-1 following recognition by RIG-I and MDA5 (20). It has been previously shown that IPS-1-mediated signaling is capable of activating the NF-B signaling cascade following infection with RABV (19,20). Furthermore, transcription of pro-IL-1␤ is NF-B dependent (39).…”
Section: Il-1␤ Is Secreted After Rabv Infectionmentioning
confidence: 99%
See 1 more Smart Citation